Training to fulfill economic scale targets for UMKM products in Batujajar Transit Apartment through digital marketing - Putri Widyanti Harlina; Adhi Prapaskah Hartadi; Elazmanawati Lembong; Endah Wulandari (Community Empowerment, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a significant role in supporting economic and industrial growth. However, there are still a number of problems that need to be overcome so that MSMEs can make optimal use of technology to increase business efficiency. One of the problems faced by MSMEs is choosing the right e-commerce platform for online promotion and marketing so this service program aims to provide information in the form of counseling and training regarding digital marketing, so that by choosing the appropriate platform, MSMEs can optimize their online marketing strategy. them, reach a more precise target audience, and increase consumer satisfaction. The service method is carried out through lectures, discussions and training regarding digital marketing. The results of the service show that the group of participants who live in Batujajar transit apartments have an increased understanding regarding the importance of digital marketing, which is reflected in the participants' positive feedback during discussion and Q&A section as well as their interest in applying digital marketing concepts in MSME businesses in Batujajar transit apartments. Furthermore, at the end of this service activity, partners can continue to increase awareness of the importance of understanding and mastering knowledge about digital marketing so that they can help MSMEs reach a wider target market, increase product visibility, and increase sales significantly.